Osteopathic treatment approach to psychoemotional trauma by means of bifocal integration - Liem, Torsten; Neuhuber, Winfried (The Journal of the American Osteopathic Association, 2020)
Traumatic psychoemotional experiences often manifest in hypersympathetic states of excitement or in immobilization and withdrawal behaviors. A person with this kind of traumatic background may present with an autonomic response consistently maintained in the defensive state, which over time becomes a stressor. In this article, the authors discuss an osteopathic approach to psychoemotional trauma by means of bifocal integration, with an emphasis on promoting a relaxed body and mind by actively involving the patient in the healing process. They briefly discuss the role of mind-body therapies in treatment, considering the popular polyvagal theory and other neuropsychophysiological frameworks. The authors also focus on clinical practice, introducing the reader to the different elements of the osteopathic treatment, including the acknowledgement and integration of top-down and bottom-up dynamics in diagnosis and therapy.
CRIS-Team Scopus Importer:2020-03-06
Keywords: Emotional integration; Mind-body therapy; Psychoemotional trauma; Trauma